2018
DOI: 10.1002/gcc.22673
|View full text |Cite
|
Sign up to set email alerts
|

Array‐based CGH of primary cutaneous CD8+ aggressive EPIDERMO‐tropic cytotoxic T‐cell lymphoma

Abstract: Primary cutaneous CD8+ aggressive epidermotropic cytotoxic T‐cell lymphoma (pcAECyTCL) is a rare provisionally categorized cutaneous lymphoma characterized by an aggressive course. Its pathogenesis and molecular mechanisms are still unknown, and only two individual cases have so far been molecularly characterized. The aim of this study was to define the pattern of numerical chromosomal alterations in tumor samples taken from 20 patients with pcAECyTCL at the time of diagnosis by means of array‐comparative geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In addition, four of 12 patients experienced chromothripsis/chromoplexy-like events which mediated the deletion of relevant tumor suppressors (e.g., CDKN2C, CHD5, FAS, PTEN, etc.). In full agreement with previously published data, 5 we found that gains within 7q and 17q as well as losses within 1p and 13q were the most common largescale chromosomal imbalances. Our analysis identified a group of bona fide oncogenes and tumor suppressors with central roles in the cell cycle (i.e., CDKN2A/B, MIR34AHG, MYC, RB1, TP53), chromatin regulation (i.e., ARID1A, BAZ1A, EED, EPC1, KMT2D, NCOR1, ZEB1) and the JAK-STAT pathway (i.e., JAK2, JAK3, PTPRC, SH2B3, SOCS1, STAT3, STAT5B) whose copy number, sequence organization and/or nucleotide composition were found to be recurrently altered in our pcAECyTCL cohort.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, four of 12 patients experienced chromothripsis/chromoplexy-like events which mediated the deletion of relevant tumor suppressors (e.g., CDKN2C, CHD5, FAS, PTEN, etc.). In full agreement with previously published data, 5 we found that gains within 7q and 17q as well as losses within 1p and 13q were the most common largescale chromosomal imbalances. Our analysis identified a group of bona fide oncogenes and tumor suppressors with central roles in the cell cycle (i.e., CDKN2A/B, MIR34AHG, MYC, RB1, TP53), chromatin regulation (i.e., ARID1A, BAZ1A, EED, EPC1, KMT2D, NCOR1, ZEB1) and the JAK-STAT pathway (i.e., JAK2, JAK3, PTPRC, SH2B3, SOCS1, STAT3, STAT5B) whose copy number, sequence organization and/or nucleotide composition were found to be recurrently altered in our pcAECyTCL cohort.…”
Section: Discussionsupporting
confidence: 93%
“…1 Thus far the study of the pathogenetic basis of this malignancy has been marginal due to its rarity. Recently, a study performed on tumors from 20 patients defined the copy number alteration (CNA) profile of pcAECyTCL by using array-based comparative genomic hybridization, 5 and before this, two clinical case reports included the evaluation of CNA in single patients by using array-based methods as well. 6,7 Recurrent CNA uncovered by these studies include losses within 1p, 9p, 13q and 16p as well as gains within 7q, 8q and 17q, with loss of the region containing CDKN2A/B being the most frequent CNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pcAETCL is a rare fatal subtype of T-cell NHL presenting complex karyotype and clonal evolution that reflects genomic instability. No specific profile of recurrent CNV have been reported but gains and losses of 7q, 8q24.3, 17q and losses of 9p21.3 (CDKN2A-CDKN2B) and 17p including the TP53 gene 238,239 .…”
Section: Primary Cutaneous Cd8+ Aggressive Epidermotropic Cytotoxic T-cell Lymphoma (Pcaetcl)mentioning
confidence: 99%
“…Primary cutaneous CD8(+) aggressive epidermotropic lymphoma pcAETCL is a rare fatal subtype of T-cell NHL presenting complex karyotype and clonal evolution that reflects genomic instability. Gains of 7q, 8q24.3, 17q and losses of 9p21.3 (CDKN2A-CDKN2B) and 17p including the TP53 gene have been reported;however, very recently, the pcAETCL carries JAK2 gene fusions that may render them especially susceptible to JAK inhibitors [ 55 , 56 , 57 , 58 ].…”
Section: Other Cutaneous T-cell Lymphomas Distinct From Mycosis Fungo...mentioning
confidence: 99%